POTENSI PENGEMBANGAN KELOMPOK USAHA BERSAMA LAA TAHZAN DAN KELOMPOK USAHA BERSAMA REJEKI DI DESA MUDAL, KECAMATAN TEMANGGUNG, KABUPATEN TEMANGGUNG - Hamdani, Muliawan; Yusuf, Muhammad; Kusumaningtyas, Metta (PRESTASI, 2013)
ABSTRACT Â Mudal village is one of the villages that are within the scope of the District of Temanggung. Based on the last record, there are 54 small industries and 102 micro-scale industries (home industry). Some of the problems as described above are also faced by small industry players and households in the village Mudal, District Temanggung. The residents of this village who decided to pursue efforts to realize that such activity is a way to empower themselves and improve living standards. However, several challenges still must be faced that makes their efforts generally have not been able to realize a significant increase in the standard of living of the financial side. For this reason, various efforts that might be taken to overcome or at least minimize the impact of some of the constraints listed above should be performed. Given the fact that in general they have a weakness in terms of capital, labor, production and marketing capabilities, some villagers Mudal who runs the household scale business then decided to join in some business groups. Two business groups which are Laa Tahzan and Rejeki. Â Keywords : small and medium scale enterprises, business networking, the potential for development